2022
DOI: 10.1177/2329048x221134600
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Aneurysm Rupture in a Child with a De Novo Variant to ANKRD17

Abstract: Ankyrin repeat domain 17 (ANKRD17) is postulated to play a role in the integrity of blood vessels and has been reported to be associated with developmental delays, epilepsy, and growth restriction. Whereas ANKRD17-deficient mice have been demonstrated to experience catastrophic hemorrhages, vascular malformations have not been reported in human patients with pathogenic variants to ANKRD17. We report a term male neonate with a heterozygous de novo variant to ANKRD17 (ANKRD17; c6988 C > G, P.[P2330a]) who exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Majority of cases represent de novo mutations; however several instances of familial inheritance has been also described. 1,2 Here, we report an additional case of CAGS in a patient with previously unreported heterozygous missense variant in ANKRD17 gene. Detailed description of clinical manifestations and diagnosis are presented.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Majority of cases represent de novo mutations; however several instances of familial inheritance has been also described. 1,2 Here, we report an additional case of CAGS in a patient with previously unreported heterozygous missense variant in ANKRD17 gene. Detailed description of clinical manifestations and diagnosis are presented.…”
Section: Introductionmentioning
confidence: 80%
“… 4 ANKRD17-deficient mice models demonstrated abnormalities of embryonic development and hemorrhages with lethality. 4 Silverstein et al 2 reported a male neonate with a heterozygous missense de novo variant in ANKRD17 who experienced subarachnoid hemorrhage from a ruptured aneurysm. However, further functional analyses are needed to confirm its role in causation of cerebrovascular malformations and hemorrhages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation